Sacarose na desintoxicação de plantas de cafeeiro com deriva de glyphosate - Alecrim, Ademilson de Oliveira (2016)
Coffee culture has great importance for Brazilian economy, given that Brazil is the largest coffee producer and exporter in the world. The management of weeds is important sense they compete with the coffee plants for sunlight, water and nutrients. Chemical control is the most used, highlighting the use of glyphosate, which presents post-emergence action and is not selective to coffee. However, when applied, a drift towards the coffee plant can occur, causing great collateral effect to the culture. In this sense, many producers apply sucrose with the objective of detoxing coffee plants under the effect of glyphosate drift. The experiment was conducted in greenhouse at the Universidade Federal de Lavras (UFLA), using a completely randomized experimental design, arranged in a 3x3 factorial scheme with 2 additional treatments, in which 3 doses of sucrose (2, 4 and 8%) were applied at 3 application times (1, 24 and 168 hours after intoxication with 10% of the commercial dose of glyphosate). Regarding the additional treatments, one was not intoxicated or treated with sucrose, and the other was only intoxicated with glyphosate. After 75 days of experimentation, we evaluated growth, physiological and anatomical variables. The intoxication by glyphosate in coffee plants during the phase of implantation of the crop, impairs the growth of the shoot, however has no negative effect over the root system. For the detoxing of plants that suffered glyphosate drift during the period of implantation of the crop, sucrose must be applied in the concentration of 2%, as soon as possible (close to an hour after intoxication), with a volume of syrup in the order of 400 liters per hectare.